A new species of Coelidiana Oman (Hemiptera: Cicadellidae: Neocoelidiinae) from Brazil with key to Brazilian species, description of immature stages, and notes about parasitoids and host plant - Gonçalves, Clayton Corrêa; Silva, Jean Francisco Souza Da; Domahovski, Alexandre Cruz; Alasmar, Luísa; Paladini, Andressa (Zootaxa, 2024)
Neocoelidiinae is a subfamily of Cicadellidae endemic to the American continent with 199 valid species allocated in 36 genera and two tribes. Coelidiana comprises 23 species distributed in Central and South America. Here we describe a new species for the genus: Coelidiana aroeira sp. nov. from Paraná state, collected on Schinus terebinthifolia trees. The female genitalia for the genus are described and illustrated for the first time, and an identification key for the species occurring in Brazil is proposed. The immature stages are described and parasitism by Dryinidae (Hymenoptera) and Pipunculidae (Diptera) is reported. The new species is diagnosed by: 1) crown with four orange stripes, 2) forewing with a brown stripe, 3) male pygofer with dorsal margin with an elongate process and a dentiform process on ventral margin, 4) subgenital plates surpassing pygofer apex and fused along their length, and 5) aedeagus shaft tubular, with a single ventral atrial process fused at shaft basally.